2018
DOI: 10.1371/journal.pone.0200858
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Disease Surveillance and Response (IDSR) in Malawi: Implementation gaps and challenges for timely alert

Abstract: ObjectiveThe recent 2014 Ebola Virus Disease (EVD) outbreaks rang the bell to call upon global efforts to assist resource-constrained countries to strengthen public health surveillance system for early response. Malawi adopted the Integrated Disease Surveillance and Response (IDSR) strategy to develop its national surveillance system since 2002 and revised its guideline to fulfill the International Health Regulation (IHR) requirements in 2014. This study aimed to understand the state of IDSR implementation and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…However, one out of five health facilities missed the national guideline. Standard case definitions for case detection were better available ( Table 2) in contrast with evidence from Malawi, Uganda and Burkina Faso [23][24][25] in which printed SCDs were rarely available. All available guidelines and standard case definitions were available in English version.…”
Section: Discussionmentioning
confidence: 99%
“…However, one out of five health facilities missed the national guideline. Standard case definitions for case detection were better available ( Table 2) in contrast with evidence from Malawi, Uganda and Burkina Faso [23][24][25] in which printed SCDs were rarely available. All available guidelines and standard case definitions were available in English version.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, following the 2014–2016 West-Africa EVD outbreak, several African Member States have strengthened the implementation of the new IDSR strategy in order to improve early detection through routine surveillance [1618]. Several studies have reported improvements in disease surveillance in the African countries as a result of lessons learned from the 2014–2016 West Africa EVD outbreak [1720].…”
Section: Discussionmentioning
confidence: 99%
“…The 47 studies included in this review focused on 17 countries, ordered by number of publications: Nigeria (10 [ 14 – 23 ]), Ghana (7 [ 24 30 ]), Uganda (5 [ 31 – 35 ]), Liberia (4 [ 36 – 39 ]), the Democratic Republic of Congo (3 [ 17 , 40 , 41 ]), Ethiopia (3 [ 17 , 42 , 43 ]), Kenya (3 [ 44 46 ]), Sierra Leone (2 [ 47 , 48 ]), Zimbabwe (2 [ 49 , 50 ]), Angola (1 [ 17 ]), Botswana (1 [ 51 ]), Cameroon (1 [ 52 ]), Madagascar (1 [ 53 ]), Malawi (1 [ 54 ]), Tanzania (1 [ 17 ]), Togo (1 [ 17 ]), and Zambia (1 [ 55 ]). Four studies examined IDSR strategy on a regional level [ 56 59 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%